2008
DOI: 10.1590/s1984-29612008000100006
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of parasitism in pejerrey Odontesthes bonariensis (Atheriniformes, Atherinopsidae) from La Viña reservoir (Córdoba, Argentina)

Abstract: The pejerrey Odontesthes bonariensis is the most important freshwater fish of Argentina central region. The present study was conducted to describe the seasonal variation of parasitism in O. bonariensis from La Viña reservoir (31 degrees 17'S, 65 degrees 01'W), located in the province of Córdoba, Argentina. Between years 1999 and 2002, 573 fishes were caught, and their parasite infection and relative weight (Wr) were assesed. Three parasites were found, Lernaea cyprinacea (Crustacea), Contracaecum spp. larvae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
1
6
1
1
Order By: Relevance
“…Odontesthes bonariensis (Actinopterygii: Atherinopsidae); freshwater; intestine; adult; lakes in Buenos Aires and Córdoba Provinces; Argentina (MacDonagh 1932; Ringuelet 1943; Fuster de Plaza and Boschi 1957; Ortubay et al 1994; Mancini and Grosman 1998; Mancini et al 2008; Drago 2012; Bethular et al 2014). …”
Section: Parasite-host Listmentioning
confidence: 99%
See 1 more Smart Citation
“…Odontesthes bonariensis (Actinopterygii: Atherinopsidae); freshwater; intestine; adult; lakes in Buenos Aires and Córdoba Provinces; Argentina (MacDonagh 1932; Ringuelet 1943; Fuster de Plaza and Boschi 1957; Ortubay et al 1994; Mancini and Grosman 1998; Mancini et al 2008; Drago 2012; Bethular et al 2014). …”
Section: Parasite-host Listmentioning
confidence: 99%
“…(Mancini et al 2008), whereas MacDonagh (1932) and Ringuelet (1943) reported it as Ichthyotaenia sp.…”
Section: Parasite-host Listmentioning
confidence: 99%
“…The Argentinean silverside, Odontesthes bonariensis, is one of the most important freshwater fish for consumption and for sport fishing in the Pampas region, as well as one of the species most affected by lernaeosis (MANCINI et al, 2008a). In chronic diseases, L. cyprinacea produces serious consequences in O. bonariensis, mainly secondary bacterial infections.…”
Section: Introductionmentioning
confidence: 99%
“…Although silversides species are widely distributed, reports of parasites from wild fishes are scarce and scattered (Carballo, 2008;Carballo, Laurenti, & Cremonte, 2011;Carballo, Navone, & Cremonte, 2011;Carballo, Cremonte, Navone, & Timi, 2012;Drago, 2012;Mancini, Rodríguez, Prosperi, Salinas, & Bucco, 2006;Mancini et al, 2008;Ortubay, Semenas, Úbeda, Quaggiotto, & Viozzi, 1994). Besides publications on rearing silversides, there is no published information on their parasites (Tanzola, Semenas, & Viozzi, 2009).…”
Section: Introductionmentioning
confidence: 99%